Interdisciplinary multimodal pain treatment for patients with chronic musculoskeletal, neuropathic, primary chronic, and tumor-related pain at a university outpatient clinic-2 years follow-up in 4 symptom domains - Hölzl, Rupert; Chung, Boo Young; Benrath, Justus (The clinical journal of pain, 2025)
Objectives: - Scientific pain associations recommend that patients with chronic pain should receive specialist treatment in outpatient, day-care, or inpatient clinics by “interdisciplinary multimodal pain therapy” (IMPT). Existing structural requirements, however, can often not support a full IMPT program for diverse indications. We report on the outcomes of a modified IMPT program implemented at the Pain Center of the University Hospital Mannheim, which is readily adaptable for other regional pain centers seeing a similar broad spectrum of pain diagnoses and variable chronicities. - Methods: - The retrospective study on 106 day-care patients with chronic pain investigated the effects on 4 major pain domains (ie, pain characteristics, function and impairment, well-being and quality of life, and mental health, including depression) 2 years after program entry. Patients were categorized according to referral ICD-10 diagnoses into musculoskeletal, neuropathic, and persistent pain with psychosocial factors, plus a small group with tumor-related pain. - Results: - Most markers of the major pain domains significantly improved, including function and well-being. The improvements were reproduced in the major pain clusters, with best results for specific neuropathic and tumor pain and lesser but significant effects on musculoskeletal pain. Patients with persistent pain disorders responded least. - Discussion: - The results showed that an individualized IMPT can be put in effect in an outpatient clinic seeing a diversity of chronic pain diagnoses. The success and failure rates for different pain pictures delineate the scope and the limits of generic IMPTs.